1985
DOI: 10.1172/jci112062
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic acid polymorphism in the apolipoprotein A-1-C-III gene cluster. Association with hypertriglyceridemia.

Abstract: A DNA sequence polymorphism, revealed by digestion of human DNA with the restriction endonuclease Sst-1 and hybridization with an apolipoprotein A-I complementary DNA clone, has been shown to be located in or close to the 3' noncoding region of the apolipoprotein C-III gene. This polymorphism is found in significantly increased prevalence (P < 0.001) in Caucasian hypertriglyceridemic subjects compared with race-matched controls, and its distribution in normal individuals of differing racial origins is reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(56 citation statements)
references
References 19 publications
7
49
0
Order By: Relevance
“…We found that the distribution of different genotypes in our study subjects was closer to those reported for Chinese (4), Mayans (5), Japanese (6,7,8), Koreans (9), Taiwanese (10) Arabs (11,12). Frequency of $2 allele was also comparable which is higher in these populations as compared to those from different parts of Europe (2,3,(13)(14)(15)(16)(17), USA (18) and French (Canada) (19) (Table-2). The results corroborates with our previous findings (25).…”
Section: -38supporting
confidence: 80%
See 2 more Smart Citations
“…We found that the distribution of different genotypes in our study subjects was closer to those reported for Chinese (4), Mayans (5), Japanese (6,7,8), Koreans (9), Taiwanese (10) Arabs (11,12). Frequency of $2 allele was also comparable which is higher in these populations as compared to those from different parts of Europe (2,3,(13)(14)(15)(16)(17), USA (18) and French (Canada) (19) (Table-2). The results corroborates with our previous findings (25).…”
Section: -38supporting
confidence: 80%
“…Table-2 (18) and French (Canada) (19) populations. Most of these studies found a relationship between the presence of $2 allele and hypertriglyceridemia (2)(3)(4)(5)(6)9,11,(13)(14)(15)(16)18,(20)(21)(22). An association of this allele with CAD was also reported (26)(27)(28).…”
Section: ) Genotypic Distribution Was In Agreement Withmentioning
confidence: 97%
See 1 more Smart Citation
“…The frequency of the less common allele (S2) varies among different ethnic groups. In several case-control studies, this Sst I polymorphism has been associated with high triglyceride (HTG), similar to the Japanese population (N = 40; P < 0.025), Arabs of Kuwait (N = 38; P < 0.001) and Caucasians (N = 52; P < 0.001) (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 71%
“…The genes coding for apoA-IV, apoC-III, and apoA-I are arranged in a gene complex 3 located on human chromosome 11. In humans allelic variation in this complex has been associated with hyperlipoproteinaemia, 4 with hypertriglyceridaemia in obesity, 5 with the response of plasma lipid levels to diet, 6 and with atherosclerotic disease. 7 ApoA-IV is a component of triglyceride-rich lipoproteins, of HDL, and of the lipoprotein free plasma fraction.…”
Section: Introductionmentioning
confidence: 99%